Implementasi Data Mining Sebagai Sistem Rekomendasi Konsumen Dalam Pemilihan Smartphone - Wibisono, Angga Endra, Dedi Gunawan S.T., M.Sc (2016)
Today this community are familiar with the smartphone. Smartphone of its own development so quickly, as well as various kinds of smartphone offered to consumers from a variety of specifications and price of the smartphone. So the consumer is wavering in looking for a smartphone that will be purchased. Therefore made a recommendation system that makes it easy for the consumer in the selection of smartphones by applying data mining. Data mining can be defined for extracting new information taken from large chunk of data that helps in the decision-making process. The implementation of data mining in this research that is as system recommendations consumers in an election smartphone that can help consumers in an election smartphone who to be purchased in accordance parameter that has been provided in the system the recommendations are. Parameter used was the data smartphone purchased as variable bound ( Y ) and data age, income per month, the price smartphone, the camera back, the camera front, license and ram as variable free X1, X2, X3, X4, X5, X6, X7 . In this research in a linear regression multiple. The results of testing in this research is a system some recommendation that can help customers in an election smartphone who to be purchased in accordance parameter that is.